Various forms of corruption in the history of law - Deretić Nataša (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2012)
The paper presents an attempt to give a modest contribution to a better understanding of this phenomenon or rather 'social evil' which cannot be observed outside the contexts of time and space. Various forms of corruption were present in the states of the ancient world, as well as in the Middle Ages and the new, contemporary era. The term corruption is usually interpreted as dishonesty, bribery, or fraud which implicates it as a socially harmful phenomenon that has been in existence since 'time immemorial'. Being a widespread sociopathological and criminogenic phenomenon, corruption still calls for attention of both professionals and the general public. With the passage of time, certain forms of corruption disappeared, but new ones have appeared, developed and been perfected. This was particularly encouraged by social, economic, and political changes, especially the depression and the ensuing ethical crisis which engulfed some societies. There have always been people in certain positions of power who would take advantage of their administrative and social functions in order to gain or increase personal wealth at the cost of causing damage to the public interest. Since easy ways of getting rich are almost invariably related to corruption, an old Chinese adage remains topical even today and people should be reminded of it more often. It says: The one who has made a fortune in one year should have been hanged twelve months ago.